Tears and transformation: feeling like crying as an indicator of insightful or “aesthetic” experience with art - Pelowski, Matthew J. (Frontiers in Psychology, 2015)
This paper explores a fundamental similarity between cognitive models for crying and conceptions of insight, enlightenment or, in the context of art, “aesthetic experience.” All of which center on a process of initial discrepancy, followed by schema change, and conclude in a personal adjustment or a “transformation” of one’s image of the self. Because tears are argued to mark one of the only physical indicators of this cognitive outcome, and because the process is particularly salient in examples with art, I argue that crying may provide an intriguing marker for empirical study of perceiving art. To explore this parallel, I offer a review of crying theory as well as of tearful cases with art, pointing out the key cognitive elements. I then introduce an expanded crying model, based upon our recent model of art experience which does consider insight and adjustment or application of the self. I also consider multiple emotional and evaluative factors, which may co-vary with crying response. This theoretical discussion is then applied in three exploratory, survey-based studies, conducted within U.K., Japan and U.S. museums, and including what is claimed to be the 20th century’s most tear-inducing abstract paintings. Results showed—with cross-cultural consistency—significant correlation between “feeling like crying” and a collection of responses posited to indicate a full progression to aesthetic experience. This also found correlation to positive assessment of artwork goodness, beauty, understanding of meaning, and to final reported self reflection and epiphany. I argue that, beyond the question of why we may cry, by considering implications of what tears may indicate for information processing, feeling like crying may be a compelling basis for identifying outcomes of perceptual (art) experience.